REMAINS OF A JUVENILE PHYTOSAUR FROM THE LATE TRIASSIC OF NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
A series of nine articulated caudal vertebrae collected from the Late Norian Argillite di Riva di Solto Shale (Bergamo, Northern Italy) are described. The caudal vertebrae belong to an archosaur, most probably an immature specimen of the phytosaur Mystriosuchus, as suggested by detailed comparison with the corresponding caudal vertebrae of the adult and complete Mystriosuchus specimen collected in the same area. The new specimen is of particular interest because material unequivocally belonging to juvenile phytosaurs is very rare and it gives support to the hypothesis that the closure of the neurocentral suture in phytosaurs possibly followed the same caudal to cranial path that occurs in crocodilians.
Keywords: Caudal Vertebrae; Archosauria (Reptilia); Norian (Late Triassic); Ontogeny